Digitalisasi Dakwah: Strategi Pelatihan Media Sosial bagi MUI Kabupaten Mojokerto untuk Pemberdayaan Dai dalam Dakwah - Akbar, Ronny Makhfuddin; Sugianto, Sugianto; Sukmaningtyas, Yanuarini Nur; Syaifuddin, Ahmad (Fakultas Ekonomi Universitas Islam Majapahit, 2025)
The digital da’wah training program is part of a community service initiative aimed at empowering da’is to utilize social media as an effective platform for Islamic preaching in the digital era. This program is designed to address challenges such as low media literacy and the spread of hoaxes by equipping da’is with practical skills to create creative, informative, and engaging content. The training materials cover strategies for using digital platforms such as Instagram, TikTok, and YouTube, producing high-quality content, and techniques for enhancing audience interaction through social media features. As a result, participants are able to develop the ability to create da’wah content that is effective, relevant, and aligned with the needs of the community. This program is expected to serve as a sustainable step in promoting a moderate and peaceful Islam through innovative digital approaches.